Semiotics of the void in S. Beckett´s Waiting for Godot (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
Focused analysis of the semiotics of the void in S. Becketts Waiting forGodot, rooted largely in Aristotles Poetics, and the lead concepts proffered therein. Mythos and Pathos are revealed to over-determine the vision and universe of Beckett’s straddlers, although not fully congruent with the classical sense embedded in these notions. The very quintessence of tragedy, of the absurd, and of language as a process of disarticulation are at the core of this hermeneutical synthesis, which pits and to some extent conjoins convention and post-modernity.
Keywords: Post-modernity; contemporary French theater; theater of the absurd; tragic theater